La Moisissure et la Bactérie: Deconstructing the fable of the discovery of penicillin by Ernest Duchesne. Issue 3 (September 2016) - Shama, Gilbert
Highlights: Claims have been made that Ernest Duchesne was the true discoverer of penicillin. The evidence shows that the likelihood that he worked with penicillin is low. The most persuasive evidence relates to his use of guinea pigs in experiments. Abstract : Ernest Duchesne (1874–1912) completed his thesis on microbial antagonism in 1897 in Lyon. His work lay unknown for fifty years, but on being brought to light led to his being credited with having discovered penicillin prior to Alexander Fleming. The claims surrounding Duchesne are examined here both from the strictly microbiological perspective, and also for what they reveal about how the process of discovery is frequently misconstrued. The combined weight of evidence presented here militates strongly against the possibility that the species of Penicillium that Duchesne worked with produced penicillin.